Lions Are Awesome ! - Lisa J. Amstutz (Raintree, 2016)
Africa's wild animals are awesome! Bold, vibrant photos and engaging text bring readers up close with lions. Includes information on habitat, behaviour, life cycle, and threats to these amazing creatures.
Keywords: Easy Read Non Fiction -- Easy Read Non Fiction; Living Things -- Living Things; Land Animals -- Land Animals